PENERAPAN STANDAR PELAPORAN KEUANGAN SERTA HUBUNGANNYA DENGAN ETIKA DAN TATA KELOLA PERUSAHAAN - Ayuk Yuliana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to describe and analyze the application of financial reporting standards and their relationship with ethics and corporate governance. The method used is qualitative research data reduction method with the type of research that is descriptive statistics and the data used is secondary data. The results of this study indicate that the application of General SAK has been applied to companies, especially companies listed on the IDX, but the implementation of SAK ETAP, SAK EMKM, and SAK Syariah has not been maximized. There are still many entities that do not comply with applicable standards in compiling company performance reports. This is due to limitations and what stands out is due to limited quality of human resources in the entity. Meanwhile, in the implementation of financial recording and reporting, there is ethics from an accountant that needs to be considered because accountants will often be faced with problems in the form of ethical dilemmas. As in making reporting decisions, accountants will be faced with choices that create a dilemma so that accountants need to have a reference in the form of a code of ethics to be accountable for the decisions they have taken. The existence of ethical dilemmas that cannot be resolved will cause an imbalance in the company and make the management of a company not run optimally.